2010
DOI: 10.1007/s10552-010-9574-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of second primary malignancies following nasopharyngeal carcinoma in Hong Kong

Abstract: Nasopharyngeal carcinoma (NPC) is rare in most of the world but common among southeast Asians. Since NPC is usually diagnosed at relatively young ages and most patients now survive, the issue of second primary tumors (SPTs) has become important. Previous studies of SPTs among NPC survivors have given conflicting results. Data on patients with NPC diagnosed between 1996 and 2002 were abstracted from the medical records of two Hong Kong oncology centers. SPT incidence in these patients was compared to that of Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 24 publications
4
28
1
Order By: Relevance
“…Given the male:female ratio of 2.48:1 in our study, the findings and demographics are fairly consistent with other studies . The results of second primary malignancies in this study agree somewhat with previous studies in Hong Kong, Taiwan, and pooled registries . However, there were more white patients and squamous cell carcinoma index of NPCs in our cohort, reflecting country variations and less Epstein–Barr virus‐related NPC.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Given the male:female ratio of 2.48:1 in our study, the findings and demographics are fairly consistent with other studies . The results of second primary malignancies in this study agree somewhat with previous studies in Hong Kong, Taiwan, and pooled registries . However, there were more white patients and squamous cell carcinoma index of NPCs in our cohort, reflecting country variations and less Epstein–Barr virus‐related NPC.…”
Section: Discussionsupporting
confidence: 92%
“…In our cohort, however, we did not have a significant elevated risk of lymphoma/leukemia reported by the other studies, but as these other studies did not comment on baseline histological characteristics of their NPC cohorts, this may reflect that our cohort represented only those with a histology of squamous cell carcinoma or lymphoepithelial carcinoma, excluding those with other histological characteristics in NPC. Differing from the hospital‐based study from Taiwan, we did find a significantly increased risk of lung and bronchus carcinoma similar to the hospital‐based study in Hong Kong, the differences found may represent population, ethnic differences, or differences between hospital‐based and registry‐based studies. This could also represent etiological differences as more squamous cell carcinoma than undifferentiated carcinoma NPC was seen in our cohort and the effect of field cancerization of the aerodigestive tract.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…However, some patients who develop second primary tumors may be treated at local community hospitals rather than present again or return to the regional cancer center. These may be the main factors for the lower rate of second primary tumors compared with other studies . The estimated rate may be lower than the actual incidence because a proportion of patients were lost to follow‐up or died before disease progression to the second primary tumor.…”
Section: Discussionmentioning
confidence: 90%